Wireframing for everyone - Angeles, Michael; Barnard, Leon; Carlson, Billy (A Book Apart, 2023)
Many UX techniques fall apart in the real world of overflowing backlogs, two-week sprints, and stubborn stakeholders. Yet wireframing persists, despite its much-anticipated demise. Wireframes are fast and easy to make, can be created and understood by anyone, and function as both creative ideation and practical communication tools. Leaning on decades of collective experience, Michael Angeles, Leon Barnard, and Billy Carlson show us how to use low-fidelity design to generate ideas, encourage feedback, and involve everyone in the process. This approachable book also harnesses wireframing to demystify UI design, so that anyone can join in creating successful digital products.